An experimental study on emission of a diesel engine fuelled with SME (safflower methyl ester) and diesel fuel - Hazar, Hanbey; Telceken, Tugay; Sevinc, Huseyin (Pergamon-Elsevier Science Ltd, 2022)
In this study, safflower methyl ester (SME), which is an alternative fuel, was obtained from safflower seed oil (SO) for a CI engine by using transesterification method. The use of the produced fuel in an air-cooled single-cylinder diesel engine was investigated. The obtained SME was blended with diesel fuel at the rate of 20% and 50% (vol.) and also 100% SME was used. BSFC, NOx, CO, smoke density, HC, EGT, BTE, vibration and thermal image analyses were made in the test engines. In the first stage, diesel and SME fuel mixtures were used in the test engine volumetrically. In the second stage, the experiments were repeated by coating the combustion chamber elements of the same engine with chromium oxide by plasma spray method. It was determined that BSFC, CO, smoke and HC decreased but NOx, BTE, EGT and vibration increased in all test fuels in the coated engine compared to the standard engine. CO, HC, and smoke emission values of SME and its mixtures decreased except for BTE, BSFC, and NOx compared to diesel fuel. Safflower seeds can be grown easily in many parts of the world and can be considered as an alternative fuel for diesel engines. (C) 2021 Published by Elsevier Ltd.
Keywords: Thermal barrier coating; Biodiesel; Safflower seed oil; Diesel engine; Performance; Exhaust emissions